Relationship Between Behavior of Learning and Student Achievement in Physics Subject (Jurnal Pendidikan Fisika Indonesia, 2020)
Behavioral problems become special attention to learning. Some teachers confronted with a variety of student behaviors and varied learning outcomes. This research was aimed to determine the relationship between learning outcomes and student learning behavior with ranking score. A total of 91 of 10th-grade students with three different classes became respondents. The research was used Mixed methods with the sequential explanatory approach. Quantitative data were obtained by giving multiple-choice questions. The interview method was used to collect qualitative data. Kruskal Wallis test was used to analyze quantitative data and the interview transcript analyzed by the keyword of student behavior in learning physics. The results show that behavior while learning is very significant towards student learning outcomes. Interview findings show that student behavior during the learning process could affect learning outcomes.